Toward a Responsive Legal Framework: Addressing Transaction Security Risks in Indonesia’s Digital Banking Services - Haykal, Hassanain (International Journal of Law and Society, 2025)
This study analyses the types and characteristics of these risks and evaluates the effectiveness of legal protection for consumers. Using a normative legal approach, this study focuses on Law No. 10/1998 concerning Banking, Law No. 8/1999 concerning Consumer Protection, Law No. 11/2008 as amended by Law No. 19/2016 concerning Electronic Information and Transactions, Law No. 27/2022 concerning Personal Data Protection, and OJK Regulation No. 12/POJK.03/2021 concerning Commercial Banks. Legal materials are classified into primary sources (laws, regulations, court decisions), secondary sources (books, journals, scientific commentaries), and tertiary sources (dictionaries, encyclopedias) and are collected through documentary studies. Qualitative normative analysis using grammatical, systematic, teleological, and sociological legal interpretations examines the effectiveness of regulations in protecting digital banking customers. The research findings indicate that although Indonesia has a comprehensive legal framework, its enforcement is hampered by overlapping mandates, unclear technical standards, weak interagency coordination, and limited consumer digital literacy. To address these gaps, this study proposes the Integrated Risk Responsive Approach (URRA), which integrates legal clarity, technical protections, and consumer empowerment into a harmonised governance model. The URRA provides preventive, adaptive, and restorative mechanisms that enhance public trust and system resilience. This study theoretically contributes by offering an integrated consumer protection model and guiding regulators and banks toward a coordinated, consumer-centric strategy. Limitations include reliance on normative and secondary data, highlighting the need for future empirical validation and cross-jurisdictional studies to test the implementation and effectiveness of the URRA in the rapidly evolving digital banking environment.